Find the following squares by using the identities.

(i)

(ii)

(iii)

(iv)

(v)

(vi)

(i) Using Identity

In the given expression

On substituting these values in the above identity, we get

=

(ii) Using Identity

In the given expression

On substituting these values in the above identity, we get

=

(iii) Using Identity

In the given expression

On substituting these values in the above identity, we get

=

(iv) Using Identity

In the given expression

On substituting these values in the above identity, we get

=

(v) Using Identity (a - b)^{2} = a^{2} - 2ab + b^{2}

In the given expression a =

On substituting these values in the above identity, we get

(vi) Using Identity (a + b) ^{2} = a^{2} + 2ab + b^{2}

In the given expression a =

On substituting these values in the above identity, we get

1